Pengaruh Produk Domestik Bruto Pengeluaran Pemerintah dan Tingkat Kurs terhadap Utang Luar Negeri di Indonesia - Anam, Fahrul; Prasetya, Rizal Fajar; Nikmah, Tina Khoirotun; Puspitasari, Yesi Ayu (Sahabat Publikasi, 2024)
The increase in foreign debt in Indonesia occurs almost every year. This is of course a burden on the government itself. This study aims to analyze how much influence gross domestic product, government spending and exchange rates have on Indonesia's foreign debt. The data used in this study is secondary data in the form of time series data from 2018 to 2022. The analytical method used is the classical assumption test and hypothesis testing. The classic assumption test includes the data normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. While testing the hypothesis includes the t test and f test. The results of this analysis indicate that government spending has a positive, partial and simultaneous effect on Indonesia's foreign debt. GDP and Exchange Rate have a positive effect, not partially and simultaneously have an effect on Indonesia's Foreign Debt.